A composite carbon-based solid acid-supported palladium catalyst (Pd/C-SO3H) for hydrogenolysis of plant-derived polymeric proanthocyanidins. Issue 35 (1st June 2020) - Zhu, Hongfei; Ni, Liwen; Ren, Shixue; Fang, Guizhen; Li, Shujun
Abstract : A composite catalyst, Pd/C-SO3 H, has been prepared to depolymerize plant-derived polymeric proanthocyanidins (PPC). Abstract : A composite catalyst, Pd/C-SO3 H, has been prepared to depolymerize plant-derived polymeric proanthocyanidins (PPC). Different reaction conditions were explored and the catalyst was shown to have good performance and recyclability, as well as good thermal and acid–base stability. UV, FTIR and 1 H NMR analyses showed that the depolymerization products (oligomeric proanthocyanidins, OPC) retained a condensed flavanol polyphenol structure and that the basic structural units of the polymers had not been destroyed. The antioxidant activity of the OPC was better than that of the PPC, and also better than that of 2, 6-di- tert -butyl-4-methylphenol, which is widely used in industry, including as a food additive. OPC could, therefore, be developed as a commercially useful radical chain-breaking antioxidant. The preparation of Pd/C-SO3 H provides an example of the design and development of a new composite catalyst that has high practical value. The study also provides a new technical route for the depolymerization of PPC and thus makes a useful contribution to the high-value utilization of renewable plant resources.